Sosialisasi Penggunaan Masker Respirator 6200 Kepada Petani Kratom Untuk Pengolahan Remahan - Kahar Muzakar; Hetty Sri Mulyati; Paskarada Juanti (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
The priority issue is the production of kratom leaves particularly the milling and packaging processes, on the health of the farmers. The process of grinding dried kratom leaves produces crumbles and fine dust. The fine dust produced can cause shortness of breath and red eyes. Efforts to minimize the impact of exposure to kratom dust during the grinding process and support for farmers, namely raising awareness about the use of KN95 particulate respirator masks. Providing adequate insight into kratom leaf production, focus on health forms the basis of the activities, enabling farmers to innovate in the milling and packing processes. The objective of the activity is to provide adequate insight into the safe use of masks, tested on kratom farmers, particularly during the grinding process and packing and how to use them. The activity methods consisted of surveys, field coordination, mask-wearing training, pre-test and post-test evaluations, and supervision. The results of the activity show that, based on the Wilcoxon Signed Rank Test, the average knowledge and attitude scores increased significantly, namely knowledge from 2.92 in the pre-test to 4.20 in the post-test with p value = 0.000013 (p < 0.05) and attitude values ​​also increased significantly with an average attitude score from 13.56 to 18.64 so that p value = 0.000011 (p < 0.05). These results indicate that the education provided was effective in increasing knowledge and shape a positive attitude among kratom farmers toward the use of KN95 particulate respirator masks as an effort to protect occupational health.The evaluation indicates the level of comfort in wearing a mask during the grinding process and packing did not cause shortness of breath. It does not sting the eyes and allows for longer work sessions, particularly when grinding kratom leaf fragments so that production can increase further.